Associations between challenging parenting behavior and creative tendencies of children: the chain mediating roles of positive emotion and creative self-efficacy - Shi, Dasheng; Wang, Yidi; Jin, Ruining; Chu, Lin (Frontiers in Psychology, 2024)
Background Parenting behavior has been reported to be closely associated with children’s creativity, yet the association between challenging parenting behavior and children’s creative tendencies, as well as the potential mechanisms connecting the two, remains ambiguous. Based on the Social Cognitive Theory and the Self-efficacy Theory, this study aims to examine the correlation between Chinese parents’ challenging parenting behaviors and their children’s creative tendencies, as well as the chain mediating role of children’s positive emotions and creative self-efficacy. Methods In total, 2,647 families were surveyed with questionnaires completed by parents on the Challenging Parenting Behaviors Scale and by children on the Positive/Negative Emotions Scale, the Creative Self-efficacy Scale, and the Williams Creative Tendency Test Scale, and analyzed using structural equation modeling (SEM) in SPSS 22.0 and Mplus 8.3. Results The findings indicate that challenging parenting behavior has a positive correlation with children’s positive emotions, creative self-efficacy, and creative tendencies. Through positive emotions, creative self-efficacy, and a chain mediated pathway between these two variables, challenging parenting behaviors increase children’s creative tendencies. Conclusion The favorable impacts of challenging parenting behaviors on children’s creative tendencies, with the mediating effects of children’s positive emotions and creative self-efficacy, may help Chinese parents better grasp the mechanisms underlying this association.